PEMANFAATAN ROTAN OLEH MASYARAKAT DESA MENYABO KECAMATAN TAYAN HULU KABUPATEN SANGGAU - Sinurat, Novy Sunita; M, Iskandar A; Rifanjani, Slamet (JURNAL HUTAN LESTARI, 2019)
The research aimed to find out types of rattan, types of handicrafts, and the utilization process by the craftsmen community in the village of Menyabo. The subject of the study was community in the village of Menyabo utilizing rattan. The object of research is rattan which is utlization by the community. The research method was the survey, in which the sample was taken through sampling techniques using a census from the entire craftsman community. The data were collected through an in-depth interview by referring to interview guidelines. The results of data analysis showed that there were only a few types of rattan found in Menyabo village, and only two types of rattan used, namely Marau rattan and Sega rattan. The product in the form of a bearable, takin, fork, tengkalang/basket, winnow, and shoe/sandals rack. Menyabo village community do not market the product. All types of product is only used for daily needs as kitchen furniture. Keywords: Utilization, Rattan, Community